Σ-porosity in monotonic analysis with applications to optimization. (25th May 2005) - Rubinov, A. M.
Abstract : We introduce and study some metric spaces of increasing positively homogeneous (IPH) functions, decreasing functions, and conormal (upward) sets. We prove that the complements of the subset of strictly increasing IPH functions, of the subset of strictly decreasing functions, and of the subset of strictly conormal sets areσ -porous in corresponding spaces. Some applications to optimization are given.